Books are forever: Early life conditions, education and lifetime earnings in Europe - Giorgio Brunello; Guglielmo Weber; Christoph T. Weiss (Osaka University, Institute of Social and Economic Research (ISER), 2012)
We estimate the effect of education on lifetime income in Europe, by distinguishing between individuals who lived in rural or urban areas during childhood and between individuals who had access to many or few books at age ten. We instrument years of education using reforms of compulsory education in nine different countries, and find that individuals in rural areas were most affected by the reforms. Among those affected, individuals with many books at home at age ten enjoyed substantially higher returns to their additional education. We argue that the long-lasting beneficial effects of having books at home are due to the cultural environment in the household and the development of cognitive skills rather than to the presence of short-term liquidity constraints.
Keywords: J24; 330; lifetime earnings; returns to education; Europe; Sozialisation; Kognition; Bildungschancen; Bildungsertrag; Erwerbsverlauf; Ländlicher Raum; Europa